Mad money - Acheson, James; Cohen, Jay.; DeMartini, Frank, 1962-; Gers, Glenn; Khouri, Callie; Keaton, Diane; Danson, Ted, 1947-; Holmes, Katie, 1978-; Rothenberg, Adam.; Latifah, Queen; Mister, John.; McKay, Neil.; et al. ([Silver Spring, MD] : Anchor Bay Entertainment, 2008)
Bridget, Nina and Jackie, plan to steal money from the Federal Reserve recycle them back into the economy by spending it.
Title from container.
Based on an earlier screenplay by John Mister ; and on the screenplay "Hot Money" by Neil McKay and Terry Winsor.
Special features: Commentary by director Callie Khouri; "Makin' money:" behind the scenes of Mad money; theatrical trailer.
Director of photography, John Bailey ; editor, Wendy Greene Bricmont ; music, Marty Davich, James Newton Howard ; costume designer, Susie DeSanto ; production designer, Brent Thomas.
Diane Keaton, Ted Danson, Katie Holmes, Adam Rothenberg, Queen Latifah.
MPAA rating: PG-13; for sexual material and language, and brief drug references.
Keywords: Janitors -- United States -- Drama; Paper money -- United States -- Drama; Banks and banking -- United States -- Drama; Bank robberies -- United States -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired; Feature films; Comedy -- Feature; Crime -- Feature; Comedy films